IMPLEMENTATION OF WASTE REDUCTION POLICIES AND SWEDISH ZERO WASTE MANAGEMENT IN INDONESIA TO REALIZE RESPONSIBLE CONSUMPTION AND PRODUCTION SDGS - Amirulkamar, Said; Safirussalim; Mayzar Mulya, Sayed; Zhukaira, Intan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to analyze the implementation of waste reduction and Swedish zero waste management policies in Indonesia to realize SDGS-responsible consumption and production. This research uses qualitative methods with descriptive analysis, the data sources obtained come from journals, websites, Twitter, and other social media. Data analysis techniques use Nvivo 12 Plus analysis techniques. The research results show several examples of the adoption of zero waste practices from Sweden in Indonesia, namely trash cans, which were inspired by "pantbanken" in Sweden, composting, and reusing used goods. The implementation of Zero Waste in Indonesia is also guided by the policies that have been established by the government regarding the reduction of waste in realizing SDGs point 12, namely Ensuring Sustainable Consumption and Production Patterns, is still in the early stages but several initiatives have emerged in various regions such as waste banks, Zero Waste communities, Zero Waste businesses. However, there are still obstacles to implementing Zero Waste in Indonesia, including a lack of public awareness, lack of infrastructure, low industry participation, and economic challenges.